DESCRIPTIONS OF CONDYLE HEAD POSITION IN DIGITAL PANORAMIC RADIOGRAPH OF CLICKING AND NONCLICKING PATIENTS AT RSGM UNPAD DENTAL RADIOLOGY INSTALLATION - Meiryndra Syaira Putri; Farina Pramanik; Lusi Epsilawati (Dentino : Jurnal Kedokteran Gigi, 2019)
Background: Clicking is associated with the movement of condyle head and other predisposing factors. Digital panoramic radiograph may identify such condition by describing the position of head of condyle. Objective: To identify the description of condyle head position in digital panoramic radiograph of clicking and non-clicking patients at RSGM Unpad Dental Radiology Installation. Method: This was a descriptive research employing purposive sampling method to collect 31 samples of digital panoramic radiographs from 11 clicking patients and 20 non-clicking patients.  The measurement method in this research is referring to Ikeda’s (2011). Result: The average position of clicking TMJ was 1.45 mm from posterior aspect and the average position of non-clicking TMJ was 1.64 mm from superior aspect. Conclusion: It can be inferred that head of condyle’s position in digital panoramic radiographs of clicking and non-clicking patients at RSGM Unpad may change from normal position to the majority of head of condyle displacement approaching the glenoid fossa. Clicking TMJ is presented with posterior displacement while non-clicking TMJ demonstrates superior displacement.